Forging agents of the state? How political institutions impact CEO compensation in state-owned enterprises - Turturea, Roxana; Sauerwald, Steve; Heugens, Pursey P. M. A. R. (Journal of International Business Studies, 2025)
Governments worldwide use executive compensation to bond CEOs of state-owned enterprises (SOEs) to political agendas at the expense of private owners. We extend principal–principal (PP) agency theory to delve into the CEO cooption behavior of governments. First, building on the institution-based view, we theorize that political institutions shape the ability of governments to trigger PP conflicts by bonding SOE CEOs through executive compensation. Second, leveraging the comparative state capitalism literature, we conjecture that SOE CEOs who are bonded through executive compensation support strategies that are aligned with state goals. Evidence from matched samples of publicly listed firms across 20 countries supports our predictions. The effect of state ownership on CEO compensation varies substantially across countries and this variance is partly explained by the heterogeneity in political institutions. More specifically, we find that SOE CEOs enjoy higher compensation in contexts characterized by high political power and political factionalization, and low political polarization and political constraint. We also find that better-paid SOE CEOs support excessive levels of employment and corporate social performance, strategies aligned with state goals. Overall, we show that CEO compensation is a salient and effective tool used by governments to turn SOE CEOs into agents of the state.